PALERMO CONVENTION IN OUR LEGAL SYSTEM: PART OF OUR NATIONAL LAW OR MERELY A SOURCE OF LAW - Dewanto, Wisnu Aryo (Indonesian Journal of International Law, 2015)
Article 38 of the 2000 Palermo Convention sets out that the Convention will enter into force after a minimum requirement of ratifying or acceding States are fulfilled that is 40 countries. The Indonesian Government had signed the Palermo Convention on December 12, 2000 and had continued to ratify on April 20, 2009. Here the debate begins in regard with the legal status of the Convention that has been ratified by the Indonesia Government, whether the Convention applies for Indonesia or in Indonesia. In the era of Professor Mochtar Kusumaatmadja, treaties that had been ratified or acceded by the Indonesian Government would ipso facto be enforceable in Indonesia, therefore academics and practitioners convinced that Indonesia was a monist State even though in practice it never showed it. That Indonesia has been running the monism concept, I have repeatedly argued through my writings. It is because the constitutional law experts have defined and described some terms in a wrong way, such as the meaning of ratification of the Vienna Convention 1969, of approval of Parliament under Article 11 of the 1945 Indonesian Constitution, of ratification act set out by Law Nr. 24 of 2000 in regard with International Treaties as well as the meaning of self-executing and non-self-executing treaties. This paper would like to propose a different point of view on the practice of the Indonesian legal system in regard with treaties, especially the legal status of the 2000 Palermo Convention in our legal system. In addition to it, this paper also would like to identify the difference between the international obligations burdened by Indonesia as a State party, with the direct application of the Convention in our national courts, which unfortunately those two concepts are often associated with each other